Correlation between innate and adaptive immunity response in TB children post BCG vaccination. Is it effective or not?: Cross-sectional study. (May 2022) - Shabariah, Rahmini; Farsida,; Hatta, Mochammad; Patellongi, Ilhamjaya; Idris, Irfan; Santoso, Arif; Islam, Andi Asadul; Natzir, Rosdiana; Wahyudin, Bob; Warsinggih,; Sanjoyo,
Abstract: Background: How far the role of innate immunity and adaptive immunity do in children who have been BCG vaccinated in controlling the course and the severity of the TB disease has not been completely known. Mycobacterium tuberculosis entry to the body will be recognized by Toll-like receptors found on macrophages, neutrophils, and dendritic cells as part of the innate immune response, after which the dendritic cells will then present the antigen to lymphocyte T0 cells and initiate the adaptive immune response (of which CD4 T cells have an important role in). Was one or were both of these immune responses function well or not in a BCG Vaccinated Children with TB? Objective: This study aim to find a better understanding of the role of innate immune response assessed by TLR2/TLR4 mRNA gene expression and serum TLR2/TLR4 levels, while the role of adaptive immune response is assessed by analyzing serum CD4 level in children with TB who have had BCG vaccination. Methods: This cross-sectional study was conducted among children with TB at the outpatient and inpatient wards at Bhakti Medicare and Jakarta Islamic Hospital. Expression of mRNA gene was measured using the Boom method and protein serum levels were measured using the ELISA method. The results were analyzed by using the SPSS v.23 program. Results: Sixty-nine children were recruited as subjects. In this study, 68.1% of whom had BCG scars. TLR4 mRNA gene expression was found to be higher than TLR2 mRNA gene expression. Serum CD4 level was found to be highest out of TLR2 and TLR4 level, but serum TLR2 level was higher than TLR4 level. TLR2/TLR4 mRNA gene expression, serum TLR2/TLR4 levels, and CD4 levels in subjects with BCG scar were also found to be significantly higher than in subjects without BCG scar (p < 0.001). There was a significant positive correlation between TLR2/TLR4 mRNA gene expression and serum TLR2/TLR4 levels (r = 0.860; r = 0.864; p < 0.001) and between serum levels TLR2/TLR4 with serum CD4 levels (r = 0.822; r = 0.832 p < 0.001). Conclusion: As early as possible, BCG vaccine administration is needed in endemic countries, but it must be ensured that scars can be formed. It is also important to control Latent TB Infection (LTBI) to prevent transmission and relapse of disease. Highlights: For the prevention of TB disease, it is important to understand the innate and adaptive immune responses according BCG scar. Mycobacterium tuberculosis recognition by TLR as the innate immune response followed by the adaptive immune response by CD4 cells. There is a strong positive correlation between the expression of mRNA gene and the concentration of TLR and CD4 in BCG-vaccinated subjects. BCG vaccination should be done as early as possible in endemic countries, as it provides better protection against TB infection.